Comparison on water quality assessment between Skudai River and Sebulong River - Mohamad Saiful Mohamad Khir, 1994-, author; Muzaffar Zainal Abideen, supervisor; Fakulti Kejuruteraan Awam (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2016)
Project Paper (Sarjana Muda Kejuruteraan (Awam)) - Universiti Teknologi Malaysia, 2016